The fifth year of the Annals - Gastañeta, Guillermo (1922)
It has been suggested, in a solemn moment of the life of the Universidad Mayor de San Marcos, the convenience of casting a veil over the recent past of the glorious institution within which the suspension is comprised of advertising of the Annals of the Faculty of Medicine of Lima. Following the advice of the eminent teacher; while leaving the care of a calm investigation of the genesis and patterns of that time period and commentary compelled him, resumed the publication of this magazine that the domestic and foreign press always received with the greatest kindness; forcing vividly our gratitude.